Competing Selves in Madame de Lafayette's La Princesse de Montpensier and the Nouvelle Historique. Issue 3 (1st December 2021) - Patel, Nupur
Abstract: This article analyzes the different selves operating in Madame de Lafayette's La Princesse de Montpensier . Contrary to scholarship, which tends to position the text as a mere precursor of La Princesse de Clèves, it is in La Princesse de Montpensier where one first locates the interior. Lafayette presented a princess coming to terms with her identity, debating with different selves against a backdrop of social, historical, and political ideals. The nouvelle historique was central to the development of selves; it was an important medium through which Lafayette could perceive, explore, and contest a woman's identity in relation to society. The genre also enabled writers to examine themselves. Lafayette used it to test out her own authorial self and locate her place in the literary sphere.